Clinician Feedback on Using Episode Groupers with Medicare Claims Data - Thomas, Fred (CENTERS for MEDICARE & MEDICAID SERVICES, 2009)
CMS is investigating techniques that might help identify costly physician practice patterns. One method presently under evaluation is to compare resource use for certain episodes of care using commercially available episode grouping software. Although this software has been used by the private sector to classify insured individuals' medical claims into episodes of care, it has never been used with fee-for-service Medicare claims except in the studies by the Medicare Payment Advisory Commission (MedPAC) and CMS. This study reviews and reports on clinician feedback on the most obvious and important decisions that must be faced by Medicare to use grouped claims data as the foundation for a physician performance measurement system. The panel reactions show the importance of bringing persons with clinical knowledge into the development process. The clinician feedback confirms that additional research is needed.